Police use of deadly force in Brazil and the Philippines: what macro-level factors tell us - Kreuzer, Peter (PRIF reports, 2023)
This PRIF Report analyzes police use of lethal force in Brazil and the Philippines, two countries with comparatively high levels of police lethality and upward trends in recent years after political shifts toward iron-fisted policies. Based on competing explanations proposed by conflict theory and consensus theory, it analyzes how far variation can be explained by structural variables such as demography, economy, and crime levels on police use of deadly force at the subnational level. The results challenge both theories, suggesting that politics may be a relevant trigger for coercive policing.